Development of Traditional Masculinity Ideology Scale and Its Association with Ambivalent Sexism - Beril Türkoğlu; Nuray Sakallı (Psikoloji Çalışmaları)
Research in social psychology has concentrated on measuring masculinity ideology since the 1950s, primarily using samples from White and European American populations. In Türkiye, researchers have employed adapted versions of established scales such as the Male Role Norms Scale, neglecting the potential cultural nuances associated with masculinity. Addressing the research gap in non-Western cultures, we present the Traditional Masculinity Ideology Scale (TMIS), specifically tailored to the cultural context of Türkiye. In Study 1, we developed the TMIS as a novel measure, assessing its relationship with Ambivalent Sexism and Ambivalence toward Men for content and construct validity. The sample included 297 men and 294 women university students through convenient sampling. Exploratory factor analyses identified a four-factor structure for the TMIS, encompassing 22 items related to respectability/responsibility, disdain for gay men, emotional restriction, and dominance. Convergent validity was established through correlations with hostile and benevolent sexism, and hostility toward men. The low correlation between the TMIS and benevolence toward men demonstrated divergent validity. In Study 2, the four-factor structure was confirmed with 209 non-student participants (96 women and 113 men) using convenient sampling. Confirmatory factor analysis supported the bi-factor model over the second-order and single-factor models. In the bi-factor model, each item is loaded onto specific sub-factors and an overarching traditional masculinity ideology factor, eliminating hierarchy among sub-factors by accounting for shared variances. Results affirmed the TMIS’s four-factor structure and provided a global-factor measure for future applications. We discussed the intersections and divergences of the TMIS with the existing literature on masculinity measures, emphasizing its cultural relevance and potential for broader applicability.